Personalizing mobile-health Apps using social media reinforcement learning to increase physical activity among bachelor nursing students: A feseable study - Lidwina Triastuti Listianingsih; Monica Saptiningsih; Friska BR Sinaga; Fransiskus Xaverius Widiantoro (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Applying a smartphone health-App might suitable in the context of bachelor nursing students in Indonesia.Purpose: This study was conducted an smartphone health Apps and social media for bachelor nursing students to promote physical activity.Method: A quasy experiment with pre and post-test design included 80 bachelor nursing students with physical inactive by sample power to estimated, and recruited convinience samples from the nursing institutions. The eligible participants were randomly assigned to intervention or control group. The smartphone health-app group received electronic booklet of physical activity (PA) and health app combine with social media tool reinforcement during 12-week, and control group received usual care. Physical activity was measured using the questionaire and smartphone-health-app, and self-efficacy were assessed through extensive questionnaire. Data was analyzed within and between smartphone health-app and control groups to assess progarm using pair t-tests.Results: The primary outcome of promoting PA, there was a significant increase after 12-week of intervention, and significant difference between the groups was observed. The secondary outcomes, there was a significant increase in self-efficacy in both groups, and significant difference between groups.Conclusion: The intervention was successfully promoted PA of bachelor nursing students over 12-week. The intervention was designed to be simple for widespread implementation in a variety of bachelor nursing students and settings, as it requires no special equipment or previous PA knowledge.